Compositional adjustment of concurrent programs to satisfy temporal logic constraints in MENDELS ZONE - Uchihira, Naoshi; Honiden, Shinichi (The Journal of systems and software, 1996)
In this paper, we examine “program adjustment”, a formal and practical approach to developing correct concurrent programs, by automatically adjusting an imperfect program to satisfy given constraints. A concurrent program is modeled by a finite state process, and program adjustment to satisfy temporal logic constraints is formalized as the synthesis of an arbiter process which partially serializes target (i.e., imperfect) processes to remove harmful nondeterministic behaviors. Compositional adjustment is also proposed for large-scale compound target processes, using process equivalence theory. We have developed a computer-aided programming environment on the parallel computer Multi-PSI, called MENDELS ZONE, that adopts this compositional adjustment. Adjusted programs can be compiled into the kernel language (KL1) and executed on Multi-PSI.